Bodily awareness predicts functional improvement and injury risk in elite long-distance runners: a prospective study - Murofushi, K.; Mitomo, S.; Yamada, Y.; Hirohata, K.; Furuya, H.; Katagiri, H.; Akuzawa, H.; Hara, S.; Ito, M.; Kaneoka, K. (Frontiers in Psychology, 2025)
Running-related injuries (RRIs) are prevalent among long-distance athletes. Although physical conditioning remains central to preventing RRIs, bodily awareness may play an equally important role in self-regulation. The KOJI AWARENESS (KA) test was designed to enhance awareness by enabling athletes to evaluate their functional status. This study investigated whether bodily awareness, assessed by the KA test, is associated with functional improvement and reduced RRI incidence in male collegiate long-distance runners. A total of 41 male collegiate runners were recruited (mean age: 20 ± 1 years, height: 171.6 ± 5.9cm, weight: 56.6 ± 4.1kg), and 35 completed the protocol. All participants underwent pre- and post-season KA testing and performed individualized corrective exercises based on their results. Awareness of functional decline was measured at only post-season by questionnaire with a five-point Likert scale, with athletes selecting "Very aware" classified into the Excellent Awareness Group. KA scores, score changes, and RRI incidence were compared between groups. Eight runners (22.9%) demonstrated excellent awareness; this group had significantly higher post-season KA scores and greater absolute and relative improvements than the Not-Excellent Awareness Group (p < 0.05). RRI incidence was 0% in the Excellent Awareness Group and 14.8% in the other group, though the difference was not statistically significant. Overall RRI incidence was 11.4%. These findings suggest that cultivating bodily awareness strengthens the impact of corrective interventions. Awareness may act as a bridge between movement, perception, and resilience to injury in athletic performance.